Understanding trust and acceptance of automated vehicles: An exploratory simulator study of transfer of control between automated and manual driving. (October 2018) - Molnar, Lisa J.; Ryan, Lindsay H.; Pradhan, Anuj K.; Eby, David W.; St. Louis, Renée M.; Zakrajsek, Jennifer S.
Highlights: We examined how trust contributed to acceptance in a simulated driving environment. Vehicle automation offers promise for safe and accessible transportation. Trust has a strong influence on the acceptance and use of automated technology. Abstract: Vehicle automation offers promise for improving safe transportation, access to mobility, and quality of life. However, at least in the early stages of automation, human drivers remain an integral component of the system and their acceptance and use of the automated technology needs to be much better understood. One factor that has emerged as a strong influence on the acceptance and use of automated technology is trust. We used regression analyses to address two research questions. The first was: What factors are associated with the extent to which individuals report trust in automated technology after a simulated automated drive experience? The second research question was: How are trust in automated technology, control preferences (both preference for control specifically related to driving and more general preference for control), and experience with technology associated with objective measures intended to capture acceptance of automated technology? With regard to the first research question, we found that driving-specific control preferences were significantly related to reported trust. Specifically, after experiencing a simulated drive that required switching between manual and automated modes, the extent to which individuals reported that they trusted the automated technology was significantly higher among those who also reported being comfortable with other drivers behind the wheel. While specific results were mixed with regard to the second research question, we did find evidence that trust in automated driving, at least as reported after a simulated experience with the technology, was an important component of acceptance of the technology.